THE EFFECT OF CARBON EMISSIONS ON CARBON TAX: A SYSTEMATIC LITERATURE REVIEW - Mila Failasufa; Citra Triasma; Luk Luk Fuadah (LP2M IBK Nitro, 2026)
The increase in global carbon emissions has driven the adoption of carbon taxes as a fiscal policy instrument for climate change mitigation. However, the effectiveness of carbon taxes in reducing carbon emissions remains an empirical debate. This study aims to analyze the effect of carbon taxes on carbon emissions through a systematic literature review of 25 selected empirical articles from Scopus Q1-Q3 indexed journals. The synthesis results indicate that carbon taxes generally have a negative effect on carbon emissions, with effectiveness varying depending on policy design, economic characteristics, and the institutional environment. Game theory dominates as the primary analytical framework, reflecting the complexity of strategic interactions between regulators and emitters. This study concludes that carbon taxes can be an effective tool if supported by contextual policy design and integration with other climate policy instruments.